2019
DOI: 10.1177/1528083719846664
|View full text |Cite
|
Sign up to set email alerts
|

A new study on the influencing factors and mechanism of shielding effectiveness of woven fabrics containing stainless steel fibers

Abstract: Electromagnetic radiation is becoming increasingly serious around our living environment, which seriously endangers people's health and interferes with the operation of electronic equipment. The research and development of anti-electromagnetic radiation fabric have drawn more and more attention. However, the influencing rules and mechanisms of conductive fiber content, fabric tightness, warp–weft density, conductive yarn arrangement, weave type, and electromagnetic wave frequency on fabric electromagnetic shie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Therefore, Yang et al studied the effect of various structural parameters on shielding performance of fabrics and attempted to develop prediction models using extreme learning machine (ELM) algorithm taking different fabric structural parameters and their shielding performances at different frequency points as input and output variables respectively. The sensitivity analysis indicated that the prediction accuracy of the developed models had good reliability in accordance with the actual results [107,108].…”
Section: Emi Shielding Textilesmentioning
confidence: 74%
“…Therefore, Yang et al studied the effect of various structural parameters on shielding performance of fabrics and attempted to develop prediction models using extreme learning machine (ELM) algorithm taking different fabric structural parameters and their shielding performances at different frequency points as input and output variables respectively. The sensitivity analysis indicated that the prediction accuracy of the developed models had good reliability in accordance with the actual results [107,108].…”
Section: Emi Shielding Textilesmentioning
confidence: 74%
“…Liu then used the surface digital image analysis technology to analyze the surface of metal fabrics and establish the characteristic matrix, and found that the percentage content of metal fibers, porosity and arrangement direction all had a great influence on SE [66]. Yang et al [67] tested various parameters of stainless-steel fibers blended fabrics on the influence of EM shielding. The results showed that stainless steel fibers content of fabrics was positively correlated with SE, fabrics compactness was negatively correlated with S, fabric with a small difference in warp and weft density showed better SE, and the SE of bidirectional blended yarns were better than that of unidirectional blended yarns.…”
Section: The Experiments To Investigate Em Shielding Fabricsmentioning
confidence: 99%
“…However, the research of this aspect is still slow, and the existing mainly focuses on the numerical model calculation [ 4 ], structural characteristics [ 5 ], performance improvement [ 6 , 7 ], influencing factors analysis [ 8 , 9 ], test evaluation [ 10 ], new product development [ 11 , 12 ], and new mechanism research [ 13 , 14 ]. At present, improving the SE of the EMS fabric and retaining the inherent porous characteristics lack effective methods.…”
Section: Introductionmentioning
confidence: 99%